Magical realism in West African fiction : seeing with a third eye - Cooper, Brenda (Routledge research in postcolonial literatures ;, 1998)
This study contextualizes magical realism within current debates and theories of postcoloniality and examines the fiction of three of its West African pioneers: Syl Cheney-Coker of Sierra Leone, Ben Okri of Nigeria and Kojo Laing of Ghana. Brenda Cooper explores the distinct elements of the genre in a West African context, and in relation to: * a range of global expressions of magical realism, from the work of Gabriel Garcia Marquez to that of Salman Rushdie * wider contemporary trends in African writing, with particular attention to how the realism of authors such as Chinua Achebe an.